2021
DOI: 10.3390/nano11030712
|View full text |Cite
|
Sign up to set email alerts
|

Short-Pulse Lasers: A Versatile Tool in Creating Novel Nano-/Micro-Structures and Compositional Analysis for Healthcare and Wellbeing Challenges

Abstract: Driven by flexibility, precision, repeatability and eco-friendliness, laser-based technologies have attracted great interest to engineer or to analyze materials in various fields including energy, environment, biology and medicine. A major advantage of laser processing relies on the ability to directly structure matter at different scales and to prepare novel materials with unique physical and chemical properties. It is also a contact-free approach that makes it possible to work in inert or reactive liquid or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 227 publications
1
16
0
Order By: Relevance
“…In the case of optical breakdown on terbium nanoparticles consisting of only 30% oxide, there is both a maximum (75 J/cm 2 ) and a minimum (110 J/cm 2 ). For terbium nanoparticles consisting of only 5−15% oxide, only a minimum is observed at a fluence of approximately 110 J/cm 2 .…”
Section: Characterization Of Nanoparticlesmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of optical breakdown on terbium nanoparticles consisting of only 30% oxide, there is both a maximum (75 J/cm 2 ) and a minimum (110 J/cm 2 ). For terbium nanoparticles consisting of only 5−15% oxide, only a minimum is observed at a fluence of approximately 110 J/cm 2 .…”
Section: Characterization Of Nanoparticlesmentioning
confidence: 99%
“…The optical breakdown of various media began to be studied almost from the time of the advent of high-power pulsed lasers . It is known that during optical breakdown of condensed media, plasma is formed, , ultraviolet (UV), visible, and infrared (IR) radiation , and acoustic waves , are generated, and an intense chemical change of the medium itself is observed . It is known that the efficiency of laser-induced breakdown of condensed media, for example, organic solvents or water, increases significantly with the addition of small amounts of nanoparticles, especially metals .…”
Section: Introductionmentioning
confidence: 99%
“…Jaleh et al [37] reported on the recent investigations into laser-mediated synthesis of nanocomposites for environmental remediation. Al-Kattan et al [38] analysed short-pulse lasers as a versatile tool for creating novel nano-and microstructures and compositional analysis for healthcare and wellbeing challenges, respectively. Factors, such as laser ablation time and medium, affect the properties of the produced NPs [62].…”
Section: Introductionmentioning
confidence: 99%
“…Laser ablation is a method of synthesizing NPs of metals and their oxides by laser irradiation of a target metal contained in a solvent. This method makes it possible to fairly finely control the size of the resulting NPs due to the synthesis conditions (radiation parameters and the solvent used) [43][44][45][46]. Additional advantages of laser ablation are its high speed and low cost of synthesis [47].…”
Section: Introductionmentioning
confidence: 99%